Seizure susceptibility to various convulsant stimuli in the BTBR mouse model of autism spectrum disorders - Tallarico, Martina; Leo, Antonio; Russo, Emilio; Citraro, Rita; Palma, Ernesto; De Sarro, Giovambattista (Frontiers in Pharmacology, 2023)
Background: Autism spectrum disorders (ASDs) are one of the most severe chronic childhood disorders in terms of prevalence, morbidity, and impact on society. Interestingly, several systematic reviews and meta-analyses documented a bidirectional link between epilepsy and ASD, supporting the hypothesis that both disorders may have common neurobiological pathways. According to this hypothesis, an imbalance of the excitatory/inhibitory (E/I) ratio in several brain regions may represent a causal mechanism underpinning the co-occurrence of these neurological diseases. Methods: To investigate this bidirectional link, we first tested the seizure susceptibility to chemoconvulsants acting on GABAergic and glutamatergic systems in the BTBR mice, in which an imbalance between E/I has been previously demonstrated. Subsequently, we performed the PTZ kindling protocol to study the impact of seizures on autistic-like behavior and other neurological deficits in BTBR mice. Results: We found that BTBR mice have an increased susceptibility to seizures induced by chemoconvulsants impairing GABAA neurotransmission in comparison to C57BL/6J control mice, whereas no significant difference in seizure susceptibility was observed after administration of AMPA, NMDA, and Kainate. This data suggests that deficits in GABAergic neurotransmission can increase seizure susceptibility in this strain of mice. Interestingly, BTBR mice showed a longer latency in the development of kindling compared to control mice. Furthermore, PTZ-kindling did not influence autistic-like behavior in BTBR mice, whereas it was able to significantly increase anxiety and worsen cognitive performance in this strain of mice. Interestingly, C57BL/6J displayed reduced sociability after PTZ injections, supporting the hypothesis that a tight connection exists between ASD and epilepsy. Conclusion: BTBR mice can be considered a good model to study epilepsy and ASD contemporarily. However, future studies should shed light on the mechanisms underpinning the co-occurrence of these neurological disorders in the BTBR model.